Bullying Melalui Media Sosial Sebagai Tantangan Akhlak Masyarakat Modern: Analisis Q.S Al Hujurat: 11 - Putri Halimaini K; Pangulu Abdul Karim (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This article is entitled bullying through social media as a challenge to the morals of modern society (analysis of Q.s Al Hujurat: 11). This research aims to find out the phenomenon of bullying on social media as a challenge to the morals of modern society, to find out Q.S Al-Hujurat: 11 as the basis for the prohibition of bullying, to find out the definition of bullying, to find out the basic factors behind the motives of bullying perpetrators, to find out the solution to Bullying Islamic perspective. After the data is analyzed, the research results show that bullying is when a group of people repeatedly act aggressively towards one person. Allah forbids this act in Q.s al-Hujurat: 11. This verse explains the prohibition of making fun of, insulting, mocking and demeaning, especially among believers and not calling with bad titles. The solution to bullying in the perspective of the Qur'an is good prejudice, muhasabah, calling with good calls, repentance.